2012
DOI: 10.1111/j.1548-1433.2012.01421.x
|View full text |Cite
|
Sign up to set email alerts
|

Revolution, Occupation, and Love: The 2011 Year in Cultural Anthropology

Christopher Dole

Abstract: What does anthropology have to offer for making sense of the events that have come to be known as the "Arab Spring"? In this article, I use this question to organize my discussion of the prominent scholarly conversations occurring in cultural anthropology for the year 2011. The topics I consider in this review are the critical study of secularism and liberalism; affect, intimacy, and care as registers of politics and economy; space, place, and time; and indigeneity. I will suggest that last year's publications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…My impetus for this essay was that place could be a productive entryway in the comparative ethnography of late modern America. In a year‐in‐review essay, Dole () observed the same, if only in passing: “ ‘locality’ provided anthropologists writing in 2011 a thematic space to explore placemaking in North America and, namely, the forms of pleasure and fantasies of escape (from impersonal exchange, market rationalities, and the alienations of industrialized production) that take flight in consuming the ‘local' ” (231–232). In thinking about the convergence between my fieldwork with Emerging evangelicals and what I read about the ethnography of food sustainability, I pursued this essay with a suspicion that other researchers are finding different forms of place making and still other examples will soon be written about.…”
Section: Codamentioning
confidence: 99%
“…My impetus for this essay was that place could be a productive entryway in the comparative ethnography of late modern America. In a year‐in‐review essay, Dole () observed the same, if only in passing: “ ‘locality’ provided anthropologists writing in 2011 a thematic space to explore placemaking in North America and, namely, the forms of pleasure and fantasies of escape (from impersonal exchange, market rationalities, and the alienations of industrialized production) that take flight in consuming the ‘local' ” (231–232). In thinking about the convergence between my fieldwork with Emerging evangelicals and what I read about the ethnography of food sustainability, I pursued this essay with a suspicion that other researchers are finding different forms of place making and still other examples will soon be written about.…”
Section: Codamentioning
confidence: 99%
“…While geographers have written about the "atmospheres" of certain cities (Anderson 2009;Stephens 2015), anthropologists have analyzed the cultural meanings of urban space (Rotenberg 1995;Feld and Basso 1996;Low 1996). However, growing numbers of anthropologists are expanding these traditions by recognizing the importance of the sensory aspects of urban everyday life thanks to the so-called "affective turn" (Low 2006;Steward 2007;Navaro-Yashin 2007, 2012Blom Hanson and Verkaaik 2009;Dole 2011;Muehlebach and Shoshan 2012;Hennessy 2013;Wanner 2013). Here I consider the sensorial aspects of space and place in terms of how they relate to the production and transmission of affect.…”
Section: Urban Affectmentioning
confidence: 99%